IMPLEMENTASI DAN PENGARUH INOVASI PELAYANAN PUBLIK GO DIGITAL PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PROBOLINGGO - Nunung Sriwahyuni (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2023)
The dynamics and developments in the globalization era followed by the use of information technology require that public service patterns in all sectors of life undergo adjustments, both human resources, mechanisms and innovations to produce maximum public service products for the community. Law Number 24 of 2013 concerning amendments to Law Number 23 of 2006 concerning Population Administration has mandated that the Government take an active role in population administration services.This service approach is a form of providing easy, fast and free services according to the slogan of population administration services. It is expected that easy, fast and free services are not just slogans, but efforts must be made to be realized in every population document service at the Regency/City Population and Civil Registration Office, especially in Probolinggo Regency. This is because the service of population documents is one of the obligatory matters that fall under the authority of the Regional Government. However, until now the population document service is still considered poor by the community, although sometimes the fault is not solely with the Dukcapil service.